Teaching Experiences through Latin American Children's Literature - Rodríguez Vargas, Nuria (2020)
The goal of this study is to present experiences and lessons on Latin Americanchildren's literature by means of two workshops for teachers of I and IIcycles of the general basic education of the public education system in CostaRica, in the city of Heredia during 2017. The approach was to familiarizethe teacher with the Latin American children's literature through reading andanalysis of several narrative works. These works are representative of severalperiods, and socio-political and cultural contexts in our continent. Thus,we tried to develop an ability to criticize, as well as an identification withregional values and with the rescue of the Latin American historical memoryfrom the world shown in the works.